Biomechanic characteristics of target-oriented kick motions in sportive karate - Yu. P. Bredikhina; F. I. Gouzhov; L. V. Kapilevich; V. I. Andreyev (Бюллетень сибирской медицины)
The methods of electrmiography and stabilography are used to determine biomechanic characteristics of target-oriented kick motions in sportive karate. It is shown that highly qualified sportsmen can better maintain equilibrium in main karate combat maneuvers. This shows itself in the smaller amplitude of vibrations of the common center of gravity and in higher quality values of the equilibrium function compared to lower-qualification sportsmen. In addition, masters of sports show the synchronous operation of motor units, their simultaneous participation in a kick motion. The dynamics of main stabilogram and electromiogram characteristics can be used as an indicator of the level of technical training of sportsmen.